2019
DOI: 10.1007/s12325-019-01085-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Gastrointestinal Tolerability of Fumaric Acid Esters: Early Findings on Gastrointestinal Events with Diroximel Fumarate in Patients with Relapsing-Remitting Multiple Sclerosis from the Phase 3, Open-Label EVOLVE-MS-1 Study

Abstract: IntroductionDiroximel fumarate (DRF) is a novel oral fumarate in development for patients with relapsing forms of multiple sclerosis (MS). Clinical findings from the DRF development program suggest that rates of gastrointestinal (GI) treatment-emergent adverse events (TEAEs) and discontinuation due to GI TEAEs are low, based on clinical and real-world observations of other fumaric acid esters, including dimethyl fumarate (DMF). The incidence of GI TEAEs varies from 40 to 88% in clinical and real-world studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…AEs leading to DMF treatment discontinuation were GI AEs (n = 12, listed in table), depression (n = 1), and urticaria (n = 1) c One patient in the DMF arm reported an AE after the last study-dose date (post-treatment period, during the follow-up period) that led to discontinuation from the study. This patient is captured as having an AE leading to discontinuation from the study ( compared with DMF, owing to its distinct chemical structure [13]. The potential impact would likely be most evident in the upper GI tract, given that both DRF and DMF are formulated to be released from their capsules and microspheres upon traversing from the stomach into the small intestine; this region of the GI tract would be exposed to the highest concentrations of DRF and DMF, allowing for greater differentiation of their tolerability effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEs leading to DMF treatment discontinuation were GI AEs (n = 12, listed in table), depression (n = 1), and urticaria (n = 1) c One patient in the DMF arm reported an AE after the last study-dose date (post-treatment period, during the follow-up period) that led to discontinuation from the study. This patient is captured as having an AE leading to discontinuation from the study ( compared with DMF, owing to its distinct chemical structure [13]. The potential impact would likely be most evident in the upper GI tract, given that both DRF and DMF are formulated to be released from their capsules and microspheres upon traversing from the stomach into the small intestine; this region of the GI tract would be exposed to the highest concentrations of DRF and DMF, allowing for greater differentiation of their tolerability effects.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct chemical structure of DRF is hypothesized to elicit less irritation in the GI tract than DMF through lower production of methanol (a GI-irritating promoiety), and less reactivity with pre-systemic off-target proteins or receptors [13]. Interim findings from the ongoing, multicenter, 2-year, prospective, single-arm, open-label DRF phase III EVOLVE-MS-1 study have demonstrated a low rate (~ 31%) of GI AEs when considered within the context of those reported in separate clinical trials and real-world effectiveness studies of DMF [9,10,14].…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the number of side effects reported by patients reduced significantly [ 62 ]. While flushing is associated with increased prostaglandin production through key MOA agonism of HCAR2, GI symptoms are the primary reason for treatment discontinuation [ 63 , 64 ] and attributable to the action of major metabolite methanol on small intestine mucosa [ 63 ]. Progress toward improved formulations/molecules to minimise GI-related side effects, whilst maintaining the efficacy of DMF have recently been made.…”
Section: Approved Indications For Dimethyl Fumarate (Dmf)mentioning
confidence: 99%
“…DRF is hypothesized to Diroximel fumarate (DRF) in patients with relapsing-remitting multiple sclerosis: Interim safety and efficacy results from the phase 3 EVOLVE-MS-1 study produce less irritation and reactivity toward off-target receptors within the gastrointestinal (GI) tract than DMF, potentially leading to improved GI tolerability. 8 A secondary major metabolite of DRF hydrolysis is 2-hydroxyethyl succinimide (HES). HES has been studied extensively in preclinical, in vitro, and healthy volunteer studies.…”
Section: Introductionmentioning
confidence: 99%